STUDI DESKRIPTIF TENTANG PENGGUNAAN METODE INTIQOIYAH DALAM PEMBELAJARAN BAHASA ARAB DI KELAS VIII MADRASAH TSANAWIYAH NEGERI 1 INDRAGIRI HULU - Yarno Eko Saputro (STAI Nurul Falah Airmolek, 2026)
This study aims to describe the use of the Intiqoiyah method in Arabic language learning for eighth-grade students at Madrasah Tsanawiyah Negeri 1 Indragiri Hulu. The research problems include how the Intiqoiyah method is implemented, its effectiveness in improving students’ Arabic skills, and the supporting and inhibiting factors. The research method used is a qualitative approach with a descriptive study type. Data were collected through observation, interviews, and documentation. The results showed that the Intiqoiyah method was applied systematically with a gradual selection of materials, starting from simple to complex. This method had a positive impact on students’ understanding and skills, especially in reading and comprehending Arabic texts. Supporting factors included teacher readiness and adequate learning media, while inhibiting factors were the students’ varied initial abilities and limited instructional time. The novelty of this research lies in its comprehensive description of the Intiqoiyah method implementation in Arabic language teaching at the MTs level, which has rarely been explored in previous studies.